Smoking-Related Tear Film Abnormalities and Dry Eye Disease: A Meta-Analysis - Indira Putri (Archives of The Medicine and Case Reports, 2025)
Dry eye disease (DED) is a prevalent ocular condition characterized by tear film instability and ocular surface inflammation. Smoking has been identified as a potential risk factor for DED, but the impact of different smoking modalities (active, passive, and e-cigarette) on tear film and DED remains unclear. This meta-analysis aimed to evaluate the association between various forms of smoking and tear film abnormalities leading to DED. A systematic search of PubMed, Embase, and Cochrane Library databases was conducted for studies published between 2013 and 2024 investigating the effects of active smoking, passive smoking, and e-cigarette use on tear film parameters and DED diagnosis. Data extracted included tear film break-up time (TBUT), Schirmer's test results, tear osmolarity, and DED diagnostic criteria. Pooled effect estimates were calculated using random-effects models. Eight studies met the inclusion criteria, comprising 4 on active smoking, 2 on passive smoking, and 2 on e-cigarette use. Active smoking was significantly associated with reduced TBUT (standardized mean difference [SMD] = -2.87; 95% CI: -3.12 to -2.62; p<0.00001), lower Schirmer's test scores (SMD = -2.79; 95% CI: -3.23 to -2.35; p<0.00001), and increased tear osmolarity (SMD = 12.55; 95% CI: 8.17 to 16.93; p<0.00001). Passive smoking and e-cigarettes showed a similar trend but with less pronounced effects. In conclusion, this meta-analysis provides evidence that active smoking significantly impairs tear film stability and contributes to DED. Passive smoking may also have detrimental effects, while the impact of e-cigarettes requires further investigation. These findings underscore the importance of smoking cessation in DED management and public health strategies for eye health.